Prognostic impact of angiotensin-converting enzyme inhibitors and dexmedetomidine in acute respiratory distress syndrome: a MIMIC-IV-based retrospective cohort analysis - Qingli Hong; Xiaozan Yang; Huahong Yang; Xuanzhao Zhou; Jiaqi Tang; Zhongmei Wen (Frontiers in Medicine)
BackgroundAcute respiratory distress syndrome (ARDS) is a prevalent condition in the respiratory department and intensive care unit that considerably influences prognosis. Prior research has demonstrated that angiotensin-converting enzyme inhibitors (ACEIs) or dexmedetomidine can improve the prognosis of ARDS. Nonetheless, the combinatorial effect of ACEIs and dexmedetomidine on the prognosis of ARDS remains to be investigated.MethodA retrospective study was conducted using data from 696 patients with ARDS collected from the Medical Information Mart for Intensive Care IV database. Subsequently, a Cox regression model was constructed to screen for meaningful variables. Moreover, a multi-model Cox regression was constructed to exclude the interference of confounding factors and explore the effects of ACEIs alone, dexmedetomidine alone, and ACEIs combined with dexmedetomidine on the prognosis of patients with ARDS. Finally, it was verified by plotting the Kaplan–Meier survival curve.ResultThe survival rates of patients with ARDS within days 28, 60, 90, 180, and 365 after admission were 61.6, 57.0, 55.9, 53.7, and 51.3%, respectively. The results of the multi-model Cox regression revealed that compared with the application of ACEIs or dexmedetomidine alone, ACEIs combined with dexmedetomidine have a synergistic effect on reducing the risk of death in patients with ARDS. The conclusion of the Kaplan–Meier survival curve is consistent with that of the Cox regression.ConclusionIn terms of reducing the risk of death in patients with ARDS, the combined application of dexmedetomidine and ACEIs may have a better effect than monotherapy.